Management of palatal fistulas and a simple surgical algorithm proposal - DURMUŞ KOCAASLAN, FATMA NİHAL; ÇELEBİLER, ÖZHAN BEKİR (MARMARA UNIV, FAC MEDICINE, 2020)
Objectives: Despite improved techniques in repair of cleft palate, failure of healing of palatal structures resulting in a palatal fistula is one of the major challenges in the practice of reconstructive surgery. The aim of this study is to evaluate treatment success and failure in patients with palatal fistulas following cleft palate repair. Patients and Methods: Totally 44 patients with a history of cleft palate who underwent surgery for palatal fistula were included in this study undertaken between January 1999 and August 2014. Fistulas were classified as anterior and posterior according to the repair technique and were repaired using one of the following techniques: buccal mucosal flap, tongue flap or mucoperiosteal flap. Results: Success rate for anterior fistulas was 71.42% with tongue flap and 76.92% with mucoperiosteal flap. Success rate for posterior fistulas was 84.62% with mucoperiosteal flap and 75% with buccal mucosal flap. Difference in success rates between the anterior and posterior fistulas was not statistically significant. Conclusion: Our study results suggest the use of mucoperiosteal flaps for both anterior and posterior fistulas smaller than 5mm as the first choice, guided by the principle of replacing absent tissue with similar tissue.
Keywords: Cleft palate; Palatal fistula; Post-palatoplasty fistula; Tongue flap; Two-flap palatoplasty; ACELLULAR DERMAL MATRIX; CLEFT-PALATE; PRIMARY REPAIR; CLASSIFICATION; PALATOPLASTY; CLOSURE; FLAPS